2021
DOI: 10.1002/mds.28561
|View full text |Cite
|
Sign up to set email alerts
|

Claims‐Based Frailty and Outcomes: Applying an Aging Measure to Older Adults with Parkinson's Disease

Abstract: A BS TRACT: Background: Frailty is a geriatric syndrome with negative health impacts not captured by comorbidity and disability alone. The prevalence of frailty in Parkinson's disease (PD) has been described, but data on frailty-associated outcomes are limited. Objective: To describe the level of frailty and investigate the association between frailty and outcomes in a Medicare sample of persons diagnosed with PD. Methods: We used the claims-based frailty index to assess frailty in a cohort of Medicare benefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…In a claims-based cross-sectional study of 62 786 beneficiaries with PD, 55.3% were diagnosed with frailty. 17 The findings support other studies with a small sample size of patients with PD showing frailty was highly prevalent in PD. 11,13,15,16 A case-control study found significant increments in the mean number of frailty phenotypes and cumulative frailty index in patients with PD compared with controls.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In a claims-based cross-sectional study of 62 786 beneficiaries with PD, 55.3% were diagnosed with frailty. 17 The findings support other studies with a small sample size of patients with PD showing frailty was highly prevalent in PD. 11,13,15,16 A case-control study found significant increments in the mean number of frailty phenotypes and cumulative frailty index in patients with PD compared with controls.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies found that frailty was common in adults with PD. In a claims-based cross-sectional study of 62 786 beneficiaries with PD, 55.3% were diagnosed with frailty . The findings support other studies with a small sample size of patients with PD showing frailty was highly prevalent in PD .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Despite the potential overestimation of index-based methods [17], frailty has consistently been shown (regardless of the tool or definition used for its estimation) to be a significant predictor of negative outcomes, both general and disease-specific, across several different diseases, settings, and regions [4,21]. In addition, one study conducted in the US from Medicare beneficiaries reported that severe frailty was associated with higher 1-year mortality, hospitalization, emergency department visits, and fall-related injury in patients with PD [22]. A negative effect of frailty on important patient-reported outcomes such as quality of life scores in Community-Dwelling Persons with PD has also been reported [23].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors with a negative influence on survival time were sex (male), older age at the time of PD diagnosis, and higher levels of long-term care. Previous studies of PD also revealed that being male [ 4 , 20 ], older [ 4 , 20 , 21 ], and experiencing severe motor symptoms [ 21 ] and frailty [ 22 ] were associated with mortality. Although the present study only included newly diagnosed patients, a higher long-term care level at the time of diagnosis showed a shorter survival time even if the estimates were adjusted for age and comorbidity.…”
Section: Discussionmentioning
confidence: 99%